Antimicrobial efficacy of S-PRG containing toothpastes on S. mutans biofilm development - Spinola, Manuela da Silva; Mendonça, Jacqueline Landi; Garcia, Maíra Terra; Caneppele, Taciana Marco Ferraz; Junqueira, Juliana Campos; Torres, Carlos Rocha Gomes; Borges, Alessandra Buhler (Brazilian Dental Science, 2023)
Objective: to investigate the antimicrobial effects of toothpastes containing bioactive surface pre-reacted glass particles (S-PRG) on S. mutans biofilms adherence, initial colonization and maturation. Material and Methods: a reference UA 159 and a clinical S. mutans (SM6) strain were used. Bovine enamel specimens were randomly allocated into the groups (n=5): toothpastes containing 0%; 1%; 5%; 20%; 30% S-PRG; positive control dentifrice (NaF+triclosan); and negative control (distilled water). For biofilm development, samples were placed in a 24-well plate containing artificial saliva (4h), followed by adding 1mL of artificial saliva, BHI broth and 225uL of S. mutans suspension. Treatments with toothpastes were applied previously or after 4h and 24h of biofilm formation. Samples were incubated for 48h at 37°C in 5%CO2 and biofilm was detached and seeded in Petri dishes for determining the number of viable cells. Data were analyzed by ANOVA and Tukey test (5%). Results: significantly lower microorganisms’ adherence (p